2010
DOI: 10.1371/journal.pone.0010856
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Occurrence of Dosage Compensation in Candida albicans

Abstract: The important human pathogen Candida albicans possesses an unusual form of gene regulation, in which the copy number of an entire specific chromosome or a large portion of a specific chromosome changes in response to a specific adverse environment, thus, insuring survival. In the absence of the adverse environment, the altered portion of the genome can be restored to its normal condition. One major question is how C. albicans copes with gene imbalance arising by transitory aneuploid states. Here, we compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 24 publications
5
38
1
Order By: Relevance
“…Presumably, in mutants with the monosomic Ch5, a single copy of either MID1 or CNB1 is upregulated to the disomic level, whereas in mutants carrying iso-Ch5R, three copies of each of these genes are downregulated to the disomic level. We previously reported transcriptional dosage compensation on the monosomic Ch5 (28). Transcriptional dosage compensation on a trisomic chromosome will be reported elsewhere (E. Rustchenko, unpublished data).…”
Section: Fig 8 Map Of Ch5mentioning
confidence: 64%
“…Presumably, in mutants with the monosomic Ch5, a single copy of either MID1 or CNB1 is upregulated to the disomic level, whereas in mutants carrying iso-Ch5R, three copies of each of these genes are downregulated to the disomic level. We previously reported transcriptional dosage compensation on the monosomic Ch5 (28). Transcriptional dosage compensation on a trisomic chromosome will be reported elsewhere (E. Rustchenko, unpublished data).…”
Section: Fig 8 Map Of Ch5mentioning
confidence: 64%
“…We also determined that, as could be expected, the abovementioned genes are downregulated on the monosomic Ch5 in the representative tolerant mutants that were generated by exposure to caspofungin, but these genes were not downregulated when Ch5 was reduplicated. This is significant, as genes on the monosomic Ch5 can be also upregulated to the disomic or above the disomic level (31).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of gene expression in yeasts and mammals in disomics or trisomics have reported differing results as to compensation and trans-effects (e.g., refs. [35][36][37][38] vs. claims of primarily dosage effects of the varied genes (e.g., refs. 39, 40).…”
Section: Discussionmentioning
confidence: 99%